Assessing clinical outcomes of patients with acute calculous cholecystitis in addition to the Tokyo grading: A retrospective study. Issue 9 (27th June 2014) - Cheng, Wei‐Chun; Chiu, Yen‐Cheng; Chuang, Chiao‐Hsiung; Chen, Chiung‐Yu
Abstract: The management of acute cholecystitis is still based on clinical expertise. This study aims to investigate whether the outcome of acute cholecystitis can be related to the severity criteria of the Tokyo guidelines and additional clinical comorbidities. A total of 103 patients with acute cholecystitis were retrospectively enrolled and their medical records were reviewed. They were all classified according to therapeutic modality, including early cholecystectomy and antibiotic treatment with or without percutaneous cholecystostomy. The impact of the Tokyo guidelines and the presence of comorbidities on clinical outcome were assessed by univariate and multivariate regression analyses. According to Tokyo severity grading, 48 patients were Grade I, 31 patients were Grade II, and 24 patients were Grade III. The Grade III patients had a longer hospital stay than Grade II and Grade I patients (15.2 days, 9.2 days, and 7.3 days, respectively, p  < 0.05). According to multivariate analysis, patients with Grade III Tokyo severity, higher Charlson's Comorbidity Score, and encountering complications had a longer hospital stay. Based on treatment modality, surgeons selected the patients with less severity and fewer comorbidities for cholecystectomy, and these patients had a shorter hospital stay. In addition to the grading of the Tokyo guidelines, comorbidities had an additional impact on clinical outcomes and should be an important consideration when making therapeutic decisions.